Nest existences and population of Pangolin (Manis javanica Desmarest, 1822) at the designated area of Cisokan Hydropower, West Java, Indonesia - SUSANTI WITHANINGSIH; FATHIMAH NOORAHYA; ERRI N. MEGANTARA; PARIKESIT PARIKESIT; TEGUH HUSODO (Biodiversitas Journal of Biological Diversity, 2018)
Withaningsih S, Noorahya F, Megantara EN, Parikesit, Husodo T. 2018. Nest existences and population of Pangolin (Manis javanica Desmarest, 1822) at the designated area of Cisokan Hydropower, West Java, Indonesia. Biodiversitas 19: 153-162. Pangolin (Manis javanica) is one of the unique mammals found in Indonesia, which is categoryzed as protected species. However, the scientific information regarding with the population and distribution of this species is still low. Therefore, the study aimed to estimate the total population, distribution, and potential threat to Pangolin in the designated area of Cisokan Hydropower, West Java. Study was conducted using three methods; direct observation (survey) of animal signs (nest, footprint, tail print, claw marks, and feed left over), camera traps placement, and semi-structure interviews. The result shows that the active and abandoned (inactive) nests were found within the study site, and could be classified as tree nest, rock nest, and ground nest. The total population of Pangolin in Cisokan hydropower project site was estimated around 6-20 individuals. This population was distributed in five different areas; first areas were Pasir Gagak, Cigintung, Batu Nunggul, and Batu Sahulu; second area was Batu Wulung; third areas were Curug Japarana and Curug Walet; fourth areas were Hutan Gowek and Cadas Gantung; fifth area was Pongpok. The potential threats experienced by Pangolin were from illegal hunting activity and habitat fragmentation caused by infrastructure development and field clearing for crops plantation.